The Influence of Social Media Usage on Online Political Participation - Malima, Zacharia; Cabr, Mona; Samad, Ayman A El (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The purpose of this study is to determine the influence between the use of social media and online political participation. Methodology: This study uses a quantitative approach with an associative research type to analyze the influence of social media on online political participation. Data were collected through questionnaires, analyzed using SmartPLS to evaluate the measurement model, relationships between variables, and hypothesis testing, involving political science students in University of Dar es Salaam as samples. Main Findings: From the statistical results of the Analysis using Smart PLS, it was found that the intensity of social media use through political expression has a significant influence on online political participation. From the results of this study it is also known that the moderating variables that influence the relationship are media usage time, political knowledge, political affiliation and government performance. Novelty/Originality of this study: This study examines how social media has become a catalyst that expands the space for online political participation, while also offering a new perspective on the influence of algorithms and digital interaction patterns on the intensity and quality of users' political engagement.